Eradication Therapy for Pediatric Helicobacter pylori Infection - Ji-Hyun Seo; Hee-Shang Youn (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2017)
In children, Helicobacter pylori infection causes gastritis, peptic ulcer, and extraintestinal manifestations such as refractory iron deficiency anemia, failure to thrive, and chronic idiopathic thrombocytopenia. The outcomes of recommendations for H. pylori eradication therapy in children are not comparable with the eradication rates of those in adults because of the low level of evidence, including randomized placebo-controlled treatment trials. In South Korea, no standard guideline for the management of children with H. pylori infection has been established yet. Herein, we reviewed the indications for and various modalities of eradication therapy in children with H. pylori infection in accordance with a review of published articles. H. pylori-associated peptic ulcer is the only one indication for eradication therapy. A proton pump inhibitor based on a combination of two antibiotics has been considered as the standard eradication therapy in children, but no consensus has been reached regarding the modality of eradication therapy in children.